Converting the Saxons - Cragle, Joshua M., 1988- author.
1 online resource.
Keywords: "Utilizing a "crusading ethos," from 772-804 AD, Charlemagne, King of the Franks, waged war against the continental Saxons to integrate them within the growing Frankish empire and facilitate their conversion to Christianity. While substantial research has been produced concerning various components of Carolingian history, this work offers a unique examination of Charlemagne's Saxon Wars as a case study for understanding methods of conversion used in the Christianization of Europe, as well as their significance for subsequent conversion strategies employed around the globe. Converting the Saxons builds on prior scholarly research, is grounded in primary sources, and contextualized with a robust historical introduction. Throughout the text particular emphasis is given to Christian encounters with paganism and the way paganism was interpreted, confronted, and transformed. Within those encounters we observe myriad forces of coercion and incentivization used in societal religious conversion, demonstrating the need for a serious reconsideration of the standard narratives surrounding Christian missions. This book provides a scholarly and accessible resource for students and researchers interested in transhistorical methods of conversion, the history of Christianity, Early Medieval paganism, colonial religious encounters, and the nature of religious conversion"--